Cooperative Language Learning In English Language Teaching: A Review (Journal of Namibian Studies : History Politics Culture, 2023)
This research examines the Cooperative language learning as one of the effective methodologies in teaching and learning English language in terms of increasing learners’ motivation, improving the attitudes of learners toward cooperative learning, and enhancing language acquisition. By implementing the cooperative method, teachers also motivate learners to participate in all activities as well as give learners more chances to learn from friends within and between groups. Cooperative learning is a type of group occurrence, according to the behavioral perspective, because it exhibits learners based on their group's performance. The learner’s perspective focuses a strong emphasis on collaborative understandings. Social contexts have been used more frequently to influence behavior than learning, and studies on peer interaction, in general, have not revealed many academic advantages. Instead, to achieve the learning gains typical of efficient cooperative learning methods, a combination of group rewards (based on group members' learning) and peer interaction on effective learning. Additionally, the researcher suggested a few strategies for encouraging cooperative learning in English classes, such as clearly defining tasks for learners, creating an ideal setting for learning, and closely observing the groups.